This old heart: Cardiac aging and autophagy. (June 2015) - Linton, Phyllis-Jean; Gurney, Michael; Sengstock, David; Mentzer, Robert M.; Gottlieb, Roberta A.
Abstract: Autophagy, a cellular housekeeping process, is essential to maintain tissue homeostasis, particularly in long-lived cells such as cardiomyocytes. Autophagic activity declines with age and may explain many features of age-related cardiac dysfunction. In this review we summarize the current state of knowledge regarding age-related changes in autophagy in the heart. Recent findings from studies in human hearts are presented, including evidence that the autophagic response is intact in the aged human heart. Impaired autophagic clearance of protein aggregates or deteriorating mitochondria will have multiple consequences including increased arrhythmia risk, decreased contractile function, reduced tolerance to ischemic stress, and increased inflammation; thus autophagy represents a potentially important therapeutic target to mitigate the cardiac consequences of aging. This article is part of a Special Issue entitled CV Aging. Graphical abstract: Highlights: As you age autophagy slows down, debris builds up and cells turn brown. Lipofuscin the scum that marks aged cells, remnants of lysosomes gone to hell. When mitos decay they leak DNA, cytochrome c and oxo-dG. Cell death is what follows or cruel inflammation: either fate is cell in damnation. But if you recycle your organelles you'll have more years of living well.